"Powiedz mi jeszcze, za co kochasz Chopina…” Stanisława Ignacego Witkiewicza i Witolda Gombrowicza uwagi na temat odbioru muzyki - Reimann-Czajkowska, Aleksandra (Przestrzenie Teorii, 2024)
The purpose of the article “Tell me yet why you love Chopin…” Stanisław Ignacy Witkiewicz’s and Witold Gombrowicz’s remarks on the reception of music is to trace the perception of Chopin’s music literary interpreted in the works of S.I. Witkiewicz and W. Gombrowicz. Both writers presented their opinions not only in theoretical, meta-textual or paraliterary texts, but also put them in the mouths of the heroes of their novels and dramas. Literary fiction is therefore an important point of reference, proving that Witkacy and Gombrowicz’s postulates towards art, as well as the assessment of human existence, were proclaimed consistently, becoming in a way an intertextual doctrine and a superior mission. The thesis that Fryderyk Chopin and his music are an important point of reference for the views presented by Witkacy and Gombrowicz on the most important issues – art and its condition in a modern society for both writers – may seem risky. On this occasion, it is worth assuming that not only Witkacy is an art theorist, but also Gombrowicz, mainly in “Dzienniki”, lets himself to be known as an analyst of the aesthetic and philosophical order, as well as a careful observer of society, including listeners of Chopin’s works. This time the irony and grotesque present in the analyzed texts are not directed against Chopin’s music, on the contrary, they allow the music of the great romantic to be released, refuting myths and false ideas.